2007
DOI: 10.1021/jf063121c
|View full text |Cite
|
Sign up to set email alerts
|

Survey of Ethyl Carbamate in Fermented Foods Sold in the United Kingdom in 2004

Abstract: Results are presented of a survey of fermented foods and beverages sold in the United Kingdom for levels of ethyl carbamate (urethane) carried out to expand the range of food types sold in the United Kingdom for which data regarding ethyl carbamate are available. Samples were analyzed by in-house validated methods, which included measurement uncertainty estimates. The samples comprised 75 fermented liquids (beers, wines, fortified wines, spirits, liqueurs, soy sauces, and vinegars) and 25 fermented solid foods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
59
4
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 18 publications
5
59
4
2
Order By: Relevance
“…Under these conditions, many reactions can occur leading to significant changes in wine, some are crucial to the final remarkable characteristics of Madeira wine, however it may also cause production of ethyl carbamate (EC). According to Stevens and Ough [2], under fairly normal storage temperatures (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) • C), and not uncommon concentrations of urea (1-10 mg/L), a significant amount of EC will accumulate in wine.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under these conditions, many reactions can occur leading to significant changes in wine, some are crucial to the final remarkable characteristics of Madeira wine, however it may also cause production of ethyl carbamate (EC). According to Stevens and Ough [2], under fairly normal storage temperatures (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) • C), and not uncommon concentrations of urea (1-10 mg/L), a significant amount of EC will accumulate in wine.…”
Section: Introductionmentioning
confidence: 99%
“…Several extraction methodologies have been used, such as continuous liquid-liquid extraction [13], and solid phase extraction [7,14,15], combined with one-dimensional gas chromatography coupled with mass spectrometry detection (GC-MS). EC has been determined in fortified Madeira wines by SPE followed by GC-MS [15,16], and by derivatization with 9-xanthydrol, followed by high performance liquid chromatography (HPLC) [17]. More recently, a solvent-free methodology was used: solid phase microextraction (SPME) [9,18,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…51-79-6) is known for its genotoxicity but is found in a wide range of food products, including fermented foods and alcoholic beverages (e.g., stone-fruit spirits, whiskey, sake). [1][2][3][4][5][6][7] In 2007, the International Agency for Research on Cancer (IARC) upgraded ethyl carbamate to Group 2A (probably carcinogenic to humans). 8) In Japan, there are currently no regulatory limits for ethyl carbamate in food or drink.…”
mentioning
confidence: 99%
“…51-79-6) is known for its genotoxicity but is found in a wide range of food products, including fermented food and alcoholic beverages. [1][2][3][4][5][6] In 2007, the International Agency for Research on Cancer (IARC) upgraded ethyl carbamate to Group 2A (probably carcinogenic to humans). 7) The Joint FAO/WHO Expert Committee on Food Additives reported at its 64th meeting that ''The Committee concluded that intake of ethyl carbamate from foods excluding alcoholic beverages would be of low concern.…”
mentioning
confidence: 99%